Rising above crisis in turbulent times how to be resilient and agile when crisis hits - Zuraida Abal Abas; Safiyyah Ahmad Sabri; W.Omar Ali Saifuddin Wan Ismail (Coached By The Pros Series, 2021)
This books unveils stories of great industry leaders, narrated through the lens of young proteges in pursuit of achieving career excellence and developing self-worth.They learn from the best mentors through shadowing and apprenticeship, filled with valuable ideas, advice and guidance. The Coached by the Pro Series are for those who aspire to be transformational leaders and want to create a positive change in their organisation.